Development and psychometric evaluation of perceived clinical nurses' professional dignity scale: a sequential-exploratory mixed-method study - Alice Khachian; Abbas Ebadi; Marjan Mardani-Hamooleh; Hosein Bagheri; Ali Abbasi (BMC, 2023)
Abstract Background In recent years, one of the concepts that has received attention in the nursing profession is professional dignity. On the other hand, there was no proper scale to evaluate this concept. This study aimed to develop and evaluate the psychometric properties of perceived clinical nurses' professional dignity scale (PCNPDS). Methods This exploratory sequential mixed method was developed and implemented in Iran. The study was conducted in two phases; (a) item generation by hybrid concept analysis and (b) item reduction by psychometric evaluation including validity and reliability of the developed scale. Also, the interpretability (ceiling and floor effect), stability (intraclass correlation coefficient), and absolute stability (standard error of measurement) were calculated. Results 68 items in the primary item pool were finally reduced to 22 items after evaluating the validity (face, content, and construct validity) and reliability. Exploratory factor analysis revealed three factors (organizational dignity, dignity-based competency, and dignity-based appreciation) and explained 47.55% of the total extracted variance. Confirmatory factor analysis showed that the model had a good fit. Finally, Cronbach's alpha coefficient, McDonald's omega, ICC, and SEM were calculated as 0.90, 0.89, 0.96, and 1.91, respectively. Conclusion The 22-item developed scale is valid and reliable for professional dignity measurement among Iranian clinical nurses.